Análisis del fenómeno inmigratorio venezolano y su incidencia en el nivel de empleo de los ecuatorianos durante el periodo 2013-2017, caso específico la ciudad de Guayaquil - Cárdenas Arévalo, Gabriela Mercedes (2018)
This research work analyzes the Venezuelan immigration phenomenon that currently exists and its incidence in the level of employment under study (full employment and underemployment) in Ecuador from 2013 to 2017, specifically in the city of Guayaquil. Within the theoretical framework, through the collection of statistical data, they showed that from 2013 to 2017, the arrival of immigrants to Ecuador has been increasing, due to the humanitarian crisis that Venezuela is currently experiencing. In addition, the variation that Ecuador maintained in the level of employment (full employment and underemployment) was evident……